2023
DOI: 10.1186/s12916-023-02972-x
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal symptoms of long COVID-19 related to the ectopic colonization of specific bacteria that move between the upper and lower alimentary tract and alterations in serum metabolites

Abstract: Background Since the coronavirus disease 2019 (COVID-19) outbreak, many COVID-19 variants have emerged, causing several waves of pandemics and many infections. Long COVID-19, or long-term sequelae after recovery from COVID-19, has aroused worldwide concern because it reduces patient quality of life after rehabilitation. We aimed to characterize the functional differential profile of the oral and gut microbiomes and serum metabolites in patients with gastrointestinal symptoms associated with lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 70 publications
0
16
0
Order By: Relevance
“…4‐chlorophenylacetic acid, a derivative of phenylacetate, is useful for the prevention or treatment of estrogen‐sensitive breast cancer 36,37 and human neuroblastoma 38 . 4‐chlorophenylacetic is correlated with intestinal flora 39 . Recent studies have shown that calcium intake and malnutrition can lead to outbreaks of SMA and changes in the gut microbiota are associated with its severity and progression 40 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4‐chlorophenylacetic acid, a derivative of phenylacetate, is useful for the prevention or treatment of estrogen‐sensitive breast cancer 36,37 and human neuroblastoma 38 . 4‐chlorophenylacetic is correlated with intestinal flora 39 . Recent studies have shown that calcium intake and malnutrition can lead to outbreaks of SMA and changes in the gut microbiota are associated with its severity and progression 40 .…”
Section: Discussionmentioning
confidence: 99%
“… 38 4‐chlorophenylacetic is correlated with intestinal flora. 39 Recent studies have shown that calcium intake and malnutrition can lead to outbreaks of SMA and changes in the gut microbiota are associated with its severity and progression. 40 Our study showed that 4‐chlorophenylacetic acid was significantly and negatively associated with HFMSE and could be used as a marker for SMA classification.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal barrier impairment, dysbiosis of gut microbiota, and perturbation of metabolites are prevalent occurrences among individuals with COVID‐19. Extensive research has consistently shown the association between microbiota composition and the morbidity, exacerbation, and mortality rates seen in COVID‐19 patients 51–55 . The gut microbiota facilitates the assessment of sickness severity in individuals with COVID‐19 56 .…”
Section: Discussionmentioning
confidence: 99%
“…patients. [51][52][53][54][55] The gut microbiota facilitates the assessment of sickness severity in individuals with COVID-19. 56 From a mechanical standpoint, it is observed that COVID-19 disrupts the composition of gut microbiota and metabolites.…”
Section: Potential Confounding Factors and Mechanismsmentioning
confidence: 99%
“…Viruses, especially Epstein-Barr virus (EBV) hidden in the human intestine, are also an important part of the gut microbiota that can promote the occurrence and development of GBC ( Xiong et al., 2023 ; Zhang et al., 2023 ). Although viruses are extremely minuscule, they are flexible and promote tumorigenesis through different pathways involving signal transduction changes, the DNA damage response and immune regulation ( Krump and You, 2018 ).…”
Section: Viruses In Gbc Pathogenesismentioning
confidence: 99%